Age-related changes of CD4+ T cell migration and cytokine expression in germ-free and SPF mice periodontium. (March 2018) - Irie, Koichiro; Tomofuji, Takaaki; Ekuni, Daisuke; Fukuhara, Daiki; Uchida, Yoko; Kataoka, Kota; Kobayashi, Shuichiro; Kikuchi, Takeshi; Mitani, Akio; Shimazaki, Yoshihiro; Morita, Manabu
Highlights: SPF mice, but not GF mice, showed an age-related increase in alveolar bone loss. The migrated CD4 + T cell were co-expressed with IL-17A and RANKL in SPF mice. GF mice did not show age-related changes in CD4 + T cell migration and cytokine, expression. Abstract: Objective: Increasing age is a potential risk factor for periodontal tissue breakdown, which may be affected by commensal flora. The aim of this study evaluated age-related changes in CD4 + T cells, C-C chemokine ligand 5 (CCL5), interleukin (IL)-17A, and receptor activator of nuclear factor-kappa B ligand (RANKL) expression using germ-free (GF) and conventionally reared (SPF) mice. Design: GF and SPF mice at 8 (n = 6/group) and 22 weeks old (n = 6/group) were used. Immunohistochemical analyses were performed to determine the effects of aging on protein expression in periodontal tissues. Age-related changes in alveolar bone were quantified using micro-CT analysis. Results: SPF mice, but not GF mice, showed an age-related increase in alveolar bone loss ( P < 0.01). SPF mice at 22 weeks of age increased expression of CD4 + T cells, CCL5, IL-17A, and RANKL compared to those at 8 weeks of age in connective tissue and alveolar bone surface ( P < 0.01). Furthermore, there was increased CD4 + T cells, which were co-expressed with IL-17A and RANKL in SPF mice at 22 weeks of age. On the other hand, the GF mice did not show any significant differences in CD4 + T cells, CCL5, IL-17A and RANKL expression between the two age groups. Conclusions: SPF mice induced an age-related increase in CD4 + T cells co- expressed with IL-17A and RANKL, with occurring alveolar bone loss. In contrast, GF mice did not show age-related changes in CD4 + T cell migration and cytokine expression.